(untitled) (PETITUM, 2023)
ABSTRACT: This study uses empirical normative research methods. This method combines a normative approach that focuses on analyzing the rules and norms related to the National Insight program at the As’adiyah Sebatik Islamic Boarding School, as well as an empirical approach that involves collecting and analyzing empirical data obtained from field observations, interviews, and documentation studies. The results in this study of the national insight program at the As’adiyah Sebatik Islamic Boarding School have succeeded in having a positive impact on students in terms of their knowledge, attitudes and behavior related to nationality. Although the majority of students are satisfied with the program, there are several aspects that need improvement, such as facilities and instructors. Islamic religious knowledge of students plays an important role in their understanding of nationalism, and students who have a strong moderation attitude show maturity in addressing national issues. ABSTRAK: Penelitian ini menggunakan metode metode penelitian normatif empiris. Metode ini menggabungkan pendekatan normatif yang berfokus pada analisis terhadap peraturan dan norma yang terkait dengan program Wawasan Kebangsaan di Pondok Pesantren As’adiyah Sebatik, serta pendekatan empiris yang melibatkan pengumpulan dan analisis data empiris yang diperoleh dari observasi lapangan, wawancara, dan studi dokumentasi. Hasil dalam penelitian ini program wawasan kebangsaan di Pondok Pesantren As’adiyah Sebatik telah berhasil memberikan dampak positif terhadap santri dalam hal pengetahuan, sikap, dan perilaku mereka terkait kebangsaan. Meskipun mayoritas santri merasa puas dengan program, terdapat beberapa aspek yang perlu diperbaiki seperti fasilitas dan instruktur. Pengetahuan agama Islam santri berperan penting dalam pemahaman mereka tentang wawasan kebangsaan, dan santri yang memiliki sikap moderasi yang kuat menunjukkan kematangan dalam menyikapi isu-isu kebangsaan.